Simultaneous Adaptation Of Multiple Genetic Algorithm Parameters Using Fuzzy Logic Controllers - Ghallab, Abdullatif Saleh Nasser (2010)

(untitled)
This study aims at designing an online adaptive method to control multiple parameters of the Genetic Algorithm. The efficiency of Genetic Algorithm requires maintaining an appropriate balance between exploration and exploitation, which in turn greatly depends on the settings of several parameters. The parameters are not independent and have complex interactions with each other during a given run. Ignoring the interaction between the adapted parameters or adapting one single parameter may have negative impact on the other related parameters, resulting in poor performance. However, most of the available alternatives cannot solve this problem effectively. Fuzzy Adaptive Genetic Algorithm techniques have been used recently for parameter control,